2020
DOI: 10.1002/2688-8319.12015
|View full text |Cite
|
Sign up to set email alerts
|

Detecting early warnings of pressure on an African lion (Panthera leo) population in the Queen Elizabeth Conservation Area, Uganda

Abstract: 1. African lions are declining across much of their range, yet robust measures of population densities remain rare. The Queen Elizabeth Conservation Area (QECA; 2,400 km 2 ) in East Africa's Albertine Rift has potential to support a significant lion population. However, QECA lions are threatened, and information on the status of lions in the region is lacking.2. Here, we use a spatially explicit search encounter approach to estimate key population parameters of lions in the QECA. We then compare home range siz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 42 publications
2
18
0
Order By: Relevance
“…Many Ugandans have a very strong cultural and economic connection to cattle production, and with an average of 50 cows/km 2 (Cook, 2015) the country has the highest density of cattle anywhere on the continent, and the eighth highest in the world (Robinson et al, 2014). Large carnivores regularly raid cattle and other livestock (Ochieng, Ahebwa, & Visseren‐Hamakers, 2015) and are killed in retaliation through poisoning, trapping or shooting (Braczkowski et al, 2020; Tweheyo, Tumusiime, Turyahabwe, Asiimwe, & Orikiriza, 2012). Examples of this conflict include at least 19 African leopards (hereafter leopards) being killed on the boundary of the Lake Mburo National Park in a 4‐year period from 2003 to 2006 (CITES 2014), and at least 47 adult and sub‐adult lions being killed between 2006–2012 in the Queen Elizabeth Conservation Area (Braczkowski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Many Ugandans have a very strong cultural and economic connection to cattle production, and with an average of 50 cows/km 2 (Cook, 2015) the country has the highest density of cattle anywhere on the continent, and the eighth highest in the world (Robinson et al, 2014). Large carnivores regularly raid cattle and other livestock (Ochieng, Ahebwa, & Visseren‐Hamakers, 2015) and are killed in retaliation through poisoning, trapping or shooting (Braczkowski et al, 2020; Tweheyo, Tumusiime, Turyahabwe, Asiimwe, & Orikiriza, 2012). Examples of this conflict include at least 19 African leopards (hereafter leopards) being killed on the boundary of the Lake Mburo National Park in a 4‐year period from 2003 to 2006 (CITES 2014), and at least 47 adult and sub‐adult lions being killed between 2006–2012 in the Queen Elizabeth Conservation Area (Braczkowski et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The high density of hyenas, lend some support to our a priori hypothesis that they may have experienced a degree of competitive release, resultant of a decrease in lion density in the QECA (this decrease over a ten-year period is described in Braczkowski et al 2020). Creel and Creel (1996) found spotted hyenas to outnumber lions in some of Africa's largest and most pristine protected area systems (Selous, Kruger, Ngorongoro and Serengeti) on average by a ratio of 1 hyena: 0.33 lions (range=1:0.17-1:0.75).…”
Section: Hyena Densities: Are They Reflective Of Competitive Release?mentioning
confidence: 60%
“…This baseline could be of use to managers and conservation stakeholders in any future recovery efforts, however because we had only a single snapshot in time, it was impossible for us to assess whether the leopard population in the QECA is stable, decreasing or increasing. Braczkowski et al (2020) found African lion movements in the QECA had increased dramatically in the region over a ten-year period, and the proportion of females to males was low. Similarly, our leopard surveys detected a low ratio of adult female leopards in both regions of the QECA, particularly the south.…”
Section: Leopard Densitiesmentioning
confidence: 91%
See 2 more Smart Citations